Comprehensive Information Learning Training for Productive Age Mothers in the Cervical Cancer Prevention and Care Movement (GERCEP) in the Community - Lufthiani; Nasution, Siti Zahara; Karota, Evi; Siregar, Suri Mutia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Cervical cancer is the leading cause of cancer death for women in developing countries. The incidence of cervical cancer will increase four times greater in family planning acceptors who use hormonal contraceptives with a duration of more than five years. The high incidence of cervical cancer requires counseling for the community to conduct early detection of the possibility of cervical cancer. Through training and mentoring activities with comprehensive learning in productive age mother groups in the cervical cancer prevention and care Movement (GERCEP) efforts in the community that can increase knowledge as well as early prevention of cervical cancer and health maintenance efforts for productive age mothers. The method of implementing community service activities is carried out by providing education, learning training in the form of quizzing to 50 productive age mother groups. Education is carried out by providing health counseling about cervical cancer and how to prevent it through PHBS. The results of the implementation of this community service activity show that the mother's knowledge about cervical cancer and its prevention is in the good category (100%), after learning training activities. The results of the paired t-test test before and after being given learning training obtained a p value of 0.000. The results of this activity are expected that mothers are able to increase knowledge and insight in efforts to prevent cervical cancer through clean and healthy living behaviors.